LUST for mango: quantitative description of land use systems and technology for mango in Guanacaste, Costa Rica (Part A). Mango yields in relation to different management aspects - a literature study (Part B) - Ligt, L. de (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica) Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
1 fig. 8 tab. 18 ref. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE) no. 167.